2020
DOI: 10.3390/ma13102351
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Environmental Benefits Associated with the Addition of Olive Pomace in the Manufacture of Lightweight Aggregates

Abstract: A Life Cycle Assessment (LCA) using SimaPro software has been carried out concerning the manufacture of artificial lightweight aggregates (LWAs). The study aims to evaluate the changes in the environmental impact when an additive of residual origin, specifically olive pomace (OP), is added following the principles of the Circular Economy. This residue (commonly known as alperujo) was used as a substitute for clay in 1.25, 2.5 and 5 wt%. The environmental impact related to the use of olive pomace in the mixture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…De la Casa et al [56] reported the addition of alperujo to the ceramic paste of bricks, lowering density and thermal conductivity. The OP residue was also used as a substitute for clay in 1.25, 2.5 and 5% (wt) of artificial lightweight aggregate manufactures [57]. The results indicated that the addition of OP in the mixture is beneficial in terms of environmental impact compared to that related to aggregates made with clay.…”
Section: Olive Pomace and Olive Oil Mill Wastewatermentioning
confidence: 99%
“…De la Casa et al [56] reported the addition of alperujo to the ceramic paste of bricks, lowering density and thermal conductivity. The OP residue was also used as a substitute for clay in 1.25, 2.5 and 5% (wt) of artificial lightweight aggregate manufactures [57]. The results indicated that the addition of OP in the mixture is beneficial in terms of environmental impact compared to that related to aggregates made with clay.…”
Section: Olive Pomace and Olive Oil Mill Wastewatermentioning
confidence: 99%
“…Other authors [78,82] investigate the utilization of olive pomace as component for producing artificial lightweight aggregates.…”
Section: Olive Mill Waste Reused As Component In the Manufacture Of Sustainable Building Materialsmentioning
confidence: 99%
“…It constitutes around 65% of the initial weight of pressed olives, considering a three-phased pressing system, or 80% of the initial weight, considering a two-phased decanter [14,15]. It is made up of approximately 20% (w/w) olive husks and pulp and 15% (w/w) crushed olive stones, plus the residual oil and water from the olive oil extraction process [16].…”
Section: Introductionmentioning
confidence: 99%